The Stakeholders’ Acceptance Towards a New Marine Protected Areas Establishment at Pulau Sembilan, Perak - Zahari, Fadhilah; Abidin, Rahimi; Osman, Nor Hasni; Ahmad, Azhar; Apollo, Albert (2019)
Establishing a new Marine Protected Areas for sustainability often evokes the debates and conflicts from the stakeholders, particularly the local community. This study explores the acceptance of local stakeholders in Bagan Datuk concerning the proposal of a new MPA establishment at Pulau Sembilan, Perak. Data gathering employed mixed method approach. First, the interview was conducted with six respondents that represents key stakeholders’ group; followed by a survey to the local community which involves 537 respondents from 16 residential areas in Bagan Datuk. While the survey results generally show that majority of the respondents favour the proposal for MPA establishment at Pulau Sembilan, the qualitative path elucidates that the acceptance is indeed conditional upon various concerns. Among others, the issues concerning the communication with the local authorities, zoning and enforcement are the focal highlights that require further discussion. This study put forward practical implications for the corresponding agencies and interested parties that aim to protect marine areas for sustainability in the future